Prospective clinical trial of hepatitis B vaccination in adults with and without type-2 diabetes mellitus. Issue 8 (2nd August 2016) - Van Der Meeren, Olivier; Peterson, James T.; Dionne, Marc; Beasley, Richard; Ebeling, Peter R.; Ferguson, Murdo; Nissen, Michael D.; Rheault, Paul; Simpson, Richard W.; De Ridder, Marc; Crasta, Priya D.; Miller, Jacqueline M.; et al.
ABSTRACT: Objective: Patients with diabetes mellitus are at increased risk for hepatitis B virus (HBV) infection and its complications. HBV vaccination is recommended for adults with diabetes in the United States and other countries. However, few studies have assessed safety and immunogenicity of hepatitis B vaccine in such patients. We assessed the safety and immunogenicity of recombinant hepatitis B vaccine in subjects with and without diabetes mellitus. Methods : Prospective, multi-country controlled study in 21 centers (www.clinicaltrials.gov NCT01627340). Four hundred and sixteen participants with Type-2 diabetes and 258 controls matched for age and body mass index (BMI) (2:1 ratio) received 3-doses of HBV vaccine ( Engerix -B™, GSK Vaccines, Belgium) according to a 0, 1, 6 months schedule. Antibodies were measured against HBV surface antigen and expressed as seroprotection rates (anti-HBs ≥10mIU/mL) and geometric mean concentration (GMC). Results : The median age and BMI in patients with diabetes and controls (according-to-protocol cohort) were 54 y and 32.1 kg/m 2, and 53 y and 30.8 kg/m 2, respectively. Seroprotection rates (GMCs) one month post-dose-3 were 75.4% (147.6 mIU/mL) and 82.0% (384.2 mIU/mL) in patients with diabetes and controls, respectively. Age-stratified seroprotection rates for patients with diabetes were 88.5% (20–39 years), 81.2% (40–49 years), 83.2% (50–59 years), and 58.2% (≥60 years). The overall safety profile of hepatitis B vaccine was similar between groups. Conclusions : Hepatitis B vaccine is immunogenic in patients with diabetes and has a similar safety profile to vaccination in healthy controls. Because increasing age was generally associated with a reduction in seroprotection rates, hepatitis B vaccine should be administered as soon as possible after the diagnosis of diabetes.